(untitled) (Indian Journal of Arid Horticulture, 2018)
Traditional knowledge is the essence of social capital helps in the faster development of science in favour of human kind through a holistic approach. Local culture, spirit, social and ethical norms possessed by local people has often been determining factors for sustainable use, and conservation of biodiversity. In present paper, an effort has been made to converge the information on traditional knowledge generated by the tribes of Ladakh about growing and conservation of folk apricot cultivars for sustainable livelihood. To achieve this objective twenty-three major apricot growing villages of Ladakh from five different eco geographical regions i.e. Kargil, Khaltsi, Dha-Hanu, Leh and Nubra of Ladakh province have been considered. Study revealed that there were forty-three major folk apricot cultivars are grown for commercial and house hold use. The peoples of Ladakh gained location specific life-long experience and indigenous strategy for sustainable biodiversity use and management at individual as well as community level. This has been built up through regular use and attentive observations related to fresh fruit, drying and oil extraction purposes of fruits and kernels. The conserved materials of these folk cultivars are serving the country as in-situ field gene banks. Which will be a boon to the development of apricot industry leads to the enhanced livelihood and nutritional security.